Residual viremia in patients on antiretroviral therapy incorporating nevirapine is not associated with the gag‐specific cellular immune response. Issue 6 (23rd September 2013) - McIlroy, Dorian; Allavena, Clotilde; Rodallec, Audrey; Billaud, Eric; Ferré, Virginie; Raffi, François
Abstract To determine whether residual plasma viremia in HIV+ patients on nevirapine‐including antiretroviral therapy (ART) is related to anti‐HIV cellular immune responses, a case–control study was conducted comparing residual viremia in patients with detectable and undetectable Gag‐specific T‐cell responses. Gag‐specific responses were measured by IFN‐γ ELISpot. Residual viremia was determined at two consecutive hospital visits by an ultra‐sensitive technique with a detection limit of 2 copies/ml. Median residual viremia was not different in patients with a positive Gag‐specific ELISpot (n = 25) compared to those with a negative Gag‐specific ELISpot (n = 30, P = 0.91). Ten of 25 (40%) patients with consistent detectable residual viremia and 4 of 12 (33%) patients with consistently undetectable residual viremia had a positive Gag‐specific ELISpot. Undetectable residual viremia was associated with the duration of ART including nevirapine (P < 0.05), but not with the Gag‐specific ELISpot response. Gag‐specific CTL in patients on ART therefore appear to have no impact on the virus‐producing cells that are responsible for residual viremia during ART. J. Med. Virol. 86:1087–1092, 2014. © 2013 Wiley Periodicals, Inc.